Using Street Intersection Density to Model Sprawl : I-94 Corridor. - Kjos, Rachel A. (My University, 2009)
This project investigates the use of street intersection density to model urban sprawl along the Interstate 94 Corridor from Milwaukee, WI to Minneapolis/St. Paul, MN. The study analyzes changes from 1992 to 2006.
Color poster with text, map, and graphs describing analysis performed by Rachel A. Kjos, advised by J. Brady Faust.
Keywords: Interstate 94; Cities and towns--Growth; Roads--Interchanges and intersections; Posters